Sintered polymer for N-type TOPCON electronic paste as well as preparation method and application of sintered polymer
By preparing a sintered polymer for TOPCON electronic paste, the problem of gate lines falling when printing aluminum paste on the back of the TOPCON cell is solved, and adhesion and photoelectric conversion efficiency are improved.
Patent Information
- Application Number
- CN202510353257.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
During the production process of TOPCon battery cells, the probability of the gate line falling when printing aluminum paste on the back increases, resulting in a short circuit or a break in the battery cells, affecting the photoelectric conversion efficiency.
A method for preparing a sintered polymer for N-type TOPCON electronic slurry is adopted. By reacting a small molecule diol with trimellitic anhydride, a glycidyl ether and γ-glycidyl ether oxypropyl trimethoxysilane is combined to form a coupling agent-modified epoxy oligomer, and mixed with a blocked isocyanate prepolymer to form a sintered polymer with good interface wetting and flexibility.
The adhesion of TOPCON electronic paste during sintering is improved, and the probability of gate lines falling off is significantly reduced, thereby ensuring the efficient photoelectric conversion performance of the battery cell.
Smart Images

Figure CN119859235A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a sintered polymer for N-type TOPCON electronic paste and a preparation method and application thereof. Background Art
[0002] TOPCon cells are a type of high-efficiency solar cell based on tunneling oxide passivation contact technology. Its core technology is to prepare an ultra-thin oxide layer and a doped polysilicon layer on the back of the cell to form a passivation contact structure, which effectively reduces surface recombination and metal contact recombination, thereby improving cell efficiency. In recent years, TOPCon has grown rapidly as one of the mainstream photovoltaic technology routes. However, during the production process, the problem of grid line falling occurs in the metallization link, especially when aluminum paste is printed on the back, the probability of grid line falling will increase. The reasons include the diffusion of aluminum paste during sintering affecting the adhesion of silver paste, the volatilization of organic components during sintering leading to decreased adhesion, and the mismatch of shrinkage rates on both sides.
[0003] To solve the above problems, photovoltaic companies have adopted a variety of ways to improve them. One is to use laser sintering technology to reduce the impact of diffusion of aluminum paste, etc., and the other is to adjust the formula of silver paste and add materials with better adhesion to organic matter. The present invention improves the adhesion of TOPCon paste during the sintering process by creating a new structure, thereby reducing the possibility of grid line falling. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a sintered polymer for N-type TOPCON electronic paste and a preparation method and application thereof.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a sintered polymer for N-type TOPCON electronic paste, the preparation method comprising the following steps:
[0007] (1) reacting a small molecule diol with trimellitic anhydride;
[0008] (2) reacting the product obtained in step (1) with glycidyl ether;
[0009] (3) adding a coupling agent γ-glycidyloxypropyltrimethoxysilane (KH560) to the reaction system obtained in step (2) to carry out a reaction to obtain a coupling agent-modified epoxy oligomer;
[0010] (4) reacting isocyanate with polyol, and then adding a blocking agent to react to obtain a blocked isocyanate prepolymer;
[0011] (5) The coupling agent-modified epoxy oligomer is mixed with the blocked isocyanate prepolymer to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0012] The polymer prepared by the present invention can be used for N-type TOPCON electronic paste. Usually, after TOPCON is printed on the back of photovoltaic cells, when printing the silver paste on the front side, the grid lines will intermittently fall off when printing fine grids, causing partial short circuit or open circuit of the cell, thereby affecting the photoelectric conversion efficiency of the cell.
[0013] The polymer of the present invention can solve the above-mentioned problems. The epoxy modified resin part of the polymer of the present invention has good interfacial wettability with metal powder. When preparing N-type TOPCON photovoltaic modules, in the initial pre-baking stage, the coupling agent is hydrolyzed and temporarily riveted to the surface of the metal powder to combine it. When combined with the substrate silicon wafer, the blocked isocyanate has a long straight chain segment in the middle and has good flexibility. The terminal blocked isocyanate can be unblocked in the pre-baking stage, and then can be chemically combined with the residual hydroxyl group in the epoxy modified resin and the surface of the substrate, so as to form a good combination of the printed metal powder and the substrate. In the process of continuous high-temperature sintering, the cross-linked network structure formed will gradually decompose, and the main temperature for its strength reduction needs to reach above 340°C. At this time, the silver powder has been well fused and formed into a good linear structure with a certain strength, forming a good transition, thereby greatly reducing the probability of grid line falling off.
[0014] Preferably, the small molecule diol in step (1) is selected from any one of diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, or a combination of at least two thereof.
[0015] Preferably, in step (1), the molar ratio of the small molecule diol to trimellitic anhydride is 1-1.05:2, for example, 1:2, 1.01:2, 1.02:2, 1.03:2, 1.04:1 or 1.05:1.
[0016] Preferably, the reaction in step (1) is carried out in the presence of a catalyst.
[0017] Preferably, the catalyst is selected from p-toluenesulfonic acid.
[0018] Preferably, the added amount of the catalyst is 0.6-0.8% of the total mass of the small molecule diol and trimellitic anhydride, for example 0.6%, 0.63%, 0.65%, 0.68%, 0.7%, 0.73%, 0.75%, 0.78% or 0.8%.
[0019] Preferably, the reaction temperature in step (1) is 110-130°C, for example, 110°C, 115°C, 118°C, 120°C, 123°C, 125°C, 128°C or 130°C.
[0020] Preferably, the reaction in step (1) is carried out until the hydroxyl value is lower than 5 mgKOH / g (for example, the hydroxyl value is 4.8 mgKOH / g, 4.5 mgKOH / g, 4.3 mgKOH / g, 4 mgKOH / g, 3.8 mgKOH / g, 3.5 mgKOH / g, 3.0 mgKOH / g, 2.5 mgKOH / g, 2.0 mgKOH / g, 1.5 mgKOH / g, 1.0 mgKOH / g, 0.5 mgKOH / g, etc.), and the reaction is terminated.
[0021] In the present invention, the hydroxyl value is obtained by testing according to GBT 7193.2-1987 Method for Determining Hydroxyl Value of Unsaturated Polyester Resin.
[0022] Preferably, the glycidyl ether in step (2) is selected from any one of butyl glycidyl ether, dodecyl glycidyl ether and tetradecyl glycidyl ether, or a combination of at least two thereof.
[0023] Preferably, in step (2), the molar ratio of the product obtained in step (1) to the glycidyl ether is 1:2-3, for example, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.8 or 1:3.
[0024] Preferably, the reaction in step (2) is carried out in the presence of a catalyst.
[0025] Preferably, the catalyst is selected from triphenylphosphine.
[0026] Preferably, the amount of the catalyst is 2-2.5% by mass of the glycidyl ether, for example 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%.
[0027] Preferably, the reaction temperature in step (2) is 110-130°C, for example, 110°C, 115°C, 118°C, 120°C, 123°C, 125°C, 128°C or 130°C.
[0028] Preferably, the reaction in step (2) is carried out until the epoxy value is lower than 0.03eq / 100g, for example, it can be 0.028eq / 100g, 0.025eq / 100g, 0.02eq / 100g, 0.015eq / 100g, 0.01eq / 100g, etc.
[0029] In the present invention, the epoxy value is obtained by testing according to "GB / T 1677-2023 Determination of epoxy value of plasticizer".
[0030] Preferably, the amount of γ-glycidyloxypropyltrimethoxysilane added in step (3) is 1-2 times the molar amount of the product obtained in step (1), for example, 1 time, 1.2 times, 1.5 times, 1.8 times or 2 times.
[0031] Preferably, the reaction temperature in step (3) is 80-110°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, preferably 90-100°C.
[0032] Preferably, the reaction in step (3) is carried out until the acid value of the product is lower than 5 mgKOH / g (for example, the hydroxyl value is 4.8 mgKOH / g, 4.5 mgKOH / g, 4.3 mgKOH / g, 4 mgKOH / g, 3.8 mgKOH / g, 3.5 mgKOH / g, 3.0 mgKOH / g, 2.5 mgKOH / g, 2.0 mgKOH / g, 1.5 mgKOH / g, 1.0 mgKOH / g, 0.5 mgKOH / g, etc.).
[0033] In the present invention, the acid value is obtained by testing through acid-base titration.
[0034] Preferably, in step (4), the molar ratio of isocyanate to polyol is 1:0.2-0.33, for example, 1:0.2, 1:0.23, 1:0.25, 1:0.28, 1:0.3 or 1:0.33.
[0035] Preferably, the isocyanate in step (4) is selected from any one of pentamethylene diisocyanate (PDI), meta-xylylene diisocyanate (XDI) or tetramethylxylylene diisocyanate (TMXDI), or a combination of at least two thereof.
[0036] Preferably, the number average molecular weight of the polyol in step (4) is 1000-2000, for example, 1000, 1200, 1400, 1600, 1800 or 2000.
[0037] Preferably, the polyol in step (4) is selected from any one of PTMEG (polytetramethylene ether glycol) and / or PPG (polypropylene glycol), PEG (polyethylene glycol), and PO3G (polytrimethylene ether glycol), or a combination of at least two thereof.
[0038] Preferably, the polyol in step (4) is a combination of polytetramethylene ether glycol and polypropylene glycol, wherein the polytetramethylene ether glycol accounts for 40-80% of the total mass of the polyol, for example 40%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 65%, 68%, 70%, 75%, 78% or 80%.
[0039] Preferably, the temperature of the reaction of isocyanate and polyol in step (4) is 80-110°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, and the reaction time is 3-8h, for example, 3h, 4h, 5h, 6h, 7h or 8h.
[0040] Preferably, the blocking agent in step (4) is selected from any one of 3,5-dimethylpyrazole, ε-caprolactam or diisopropylamine, or a combination of at least two thereof.
[0041] Preferably, in step (4), the molar ratio of the isocyanate to the blocking agent is 1:0.72-0.85, for example, 1:0.72, 1:0.75, 1:0.78, 1:0.8, 1:0.82 or 1:0.85.
[0042] Preferably, the temperature for reacting by adding the blocking agent in step (4) is 50-80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the reaction time is 3-6h, such as 3h, 4h, 5h or 6h.
[0043] Preferably, the mixing mass ratio of the coupling agent modified epoxy oligomer to the blocked isocyanate prepolymer in step (5) is 1:0.25-0.75, for example, 1:0.25, 1:0.28, 1:0.35, 1:0.39, 1:0.46, 1:0.5, 1:0.55, 1:0.61, 1:0.67, 1:0.72 or 1:0.75.
[0044] Preferably, the mixing in step (5) is carried out at 10-30°C (eg, 10°C, 13°C, 15°C, 18°C, 20°C, 23°C, 25°C, 28°C or 30°C).
[0045] In the present invention, the reaction formula of step (1) is as follows:
[0046] ;
[0047] Among them, HO-R-OH is a small molecule diol;
[0048] The groups other than the four carboxyl groups in the product of step (1) are represented by R3, and the product of step (1) is simplified as follows: ;
[0049] When the molar ratio of the product of step (1) to glycidyl ether is 1:2, the reaction formula of step (2) is as follows:
[0050] ;
[0051] in stands for glycidyl ether;
[0052] When the molar ratio of the product of step (1) to glycidyl ether is 1:3, three carboxyl groups in the product of step (1) are reacted and one carboxyl group remains. In order to retain a portion of carboxyl groups in the product in step (2), the molar ratio of the product obtained in step (1) to glycidyl ether is controlled to be 1:2-3.
[0053] The reaction formula of step (3) is as follows:
[0054]
[0055] in It represents γ-glycidyloxypropyltrimethoxysilane.
[0056] When the product obtained in step (2) is a product with only one carboxyl group remaining, then in step (3), the remaining carboxyl group is reacted with γ-glycidyloxypropyltrimethoxysilane to form an ester.
[0057] The reaction formula of step (4) is as follows:
[0058] ;
[0059] “ "Isocyanate" " is a polyol," ” is a polyurethane prepolymer;
[0060] The reaction with the blocking agent is to react with the terminal isocyanate group, thereby completing the blocking.
[0061] On the other hand, the present invention provides a sintered polymer for N-type TOPCON electronic paste prepared by the preparation method as described above.
[0062] In another aspect, the present invention provides an N-type TOPCON electronic paste, wherein the N-type TOPCON electronic paste comprises the sintered polymer for N-type TOPCON electronic paste as described above.
[0063] On the other hand, the present invention provides an N-type TOPCON photovoltaic module, wherein the raw materials for preparing the N-type TOPCON photovoltaic module include the N-type TOPCON electronic paste as described above.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] The polymer material of the present invention is used for N-type TOPCON electronic paste, and can avoid the problem of partial short circuit or open circuit of the battery cell caused by grid line shedding when preparing photovoltaic modules, thereby ensuring that the battery cell has a higher photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 is the infrared spectrum of the product obtained in step (1) of Example 1;
[0067] Figure 2 is the infrared spectrum of the product obtained in step (2) of Example 1;
[0068] Figure 3 This is the infrared spectrum of the product obtained by the reaction of PDI with PTMEG and PPG in step (4) of Example 1;
[0069] Figure 4 This is the infrared spectrum of the blocked isocyanate prepolymer product obtained in step (4) of Example 1. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0071] The PTMEG used in the following examples has a number average molecular weight of 1000 and 2000 and is purchased from Hyosung, Korea.
[0072] PPG, number average molecular weight of 1000 and 2000, was purchased from Jiahua Chemical.
[0073] PEG, with a number average molecular weight of 1000 or 2000, is commonly available in the market.
[0074] PO3G, number average molecular weight of 1000 and 2000, was purchased from SK, South Korea.
[0075] Example 1
[0076] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0077] (1) reacting a small molecule diol, diethylene glycol, and trimellitic anhydride at a molar ratio of 1:2 at 120° C. in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.6% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0078] (2) reacting the product obtained in step (1) with n-butyl glycidyl ether in a molar ratio of 1:2 at 120° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2% of the mass of glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0079] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is 1.5 times the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 100° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0080] (4) reacting PDI with a mixed polyol of PTMEG (number average molecular weight 2000) / PPG (number average molecular weight 2000) (the mass proportion of PTMEG in the mixed polyol is 50%) at 90°C for 4 hours, wherein the molar ratio of PDI to the mixed polyol is 1:0.25, adding 3,5-dimethylpyrazole to the system after the reaction (the molar ratio of PDI to 3,5-dimethylpyrazole is 1:0.75), and reacting at 70°C for 4 hours until the NCO content is less than 0.1%, thereby obtaining a blocked isocyanate prepolymer;
[0081] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.66 at 25° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0082] The infrared spectrum of the product obtained in step (1) of this embodiment is as follows Figure 1 As shown, 1724cm -1 The characteristic absorption peak of "C=O" appeared at 2500-3600 cm -1 The broad peak is the absorption peak of the hydroxyl group in the carboxyl group on the benzene ring, 1250-1150cm -1 and 1050-1000cm -1 There is a relatively obvious CO stretching vibration absorption at 860cm -1 Left and right and 700cm -1 There is an obvious characteristic absorption peak of CH on the benzene ring.
[0083] The infrared spectrum of the product obtained in step (2) of this embodiment is as follows Figure 2 As shown, 1720cm -1 The characteristic absorption peak of "C=O" appeared at 1260cm -1 The characteristic absorption peak of COC appeared, 1150-1000cm -1 There will be obvious CO stretching vibration absorption at 850cm -1 Left and right and 700cm -1 There is a relatively obvious characteristic absorption peak of CH on the benzene ring, at 2850-2960cm -1 The CH characteristic absorption peaks of the methyl and methylene groups in the n-butyl group appeared at 3200-3600 cm -1It is the characteristic absorption peak of hydroxyl group, which proves that n-butyl glycidyl ether reacts with epoxy group and carboxyl group in the product of step (1).
[0084] The infrared spectrum of the product obtained by the reaction of PDI with PTMEG and PPG in step (4) of this embodiment is as follows: Figure 3 As shown, the -1 The characteristic absorption peak of “-NCO” appeared; 3200-3500 cm -1 The NH absorption peak appeared, 1700-1750cm -1 The C=O stretching vibration absorption peak appeared, 1000-1190cm -1 The strong absorption peak is the COC stretching vibration absorption peak.
[0085] The infrared spectrum of the blocked isocyanate prepolymer obtained in step (4) of this embodiment is as follows: Figure 4 As shown, it can be seen that 2100-2400 cm -1 The characteristic absorption peak of "-NCO" disappeared, proving that the end-capping was carried out.
[0086] Example 2
[0087] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0088] (1) reacting a small molecule diol, diethylene glycol, and trimellitic anhydride at a molar ratio of 1.05:2 at 130° C. in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.8% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0089] (2) reacting the product obtained in step (1) with dodecyl glycidyl ether in a molar ratio of 1:3 at 130° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2% of the mass of glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0090] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is 1.5 times the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 90° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0091] (4) reacting XDI with a mixed polyol of PTMEG (number average molecular weight 2000) / PPG (number average molecular weight 2000) (the mass proportion of PTMEG in the mixed polyol is 60%) at 100°C for 5 hours, wherein the molar ratio of XDI to the mixed polyol is 1:0.2, adding 3,5-dimethylpyrazole to the system after the reaction (the molar ratio of XDI to 3,5-dimethylpyrazole is 1:0.8), and reacting at 60°C for 5 hours until the NCO content is less than 0.1%, to obtain a blocked isocyanate prepolymer;
[0092] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.42 at 25° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0093] Example 3
[0094] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0095] (1) reacting a small molecule diol 1,3-propylene glycol and trimellitic anhydride at a molar ratio of 1.03:2 at 110° C. in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.6% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0096] (2) reacting the product obtained in step (1) with dodecyl glycidyl ether in a molar ratio of 1:2 at 120° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2.5% of the mass of dodecyl glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0097] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is 1.5 times the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 100° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0098] (4) reacting PDI with a mixed polyol of PTMEG (number average molecular weight 1000) / PPG (number average molecular weight 1000) (the mass proportion of PTMEG in the mixed polyol is 60%) at 80°C for 8 hours, wherein the molar ratio of PDI to the mixed polyol is 1:0.33, adding diisopropylamine to the system after the reaction (the molar ratio of PDI to diisopropylamine is 1:0.83), and reacting at 50°C for 6 hours until the NCO is less than 0.1%, to obtain a blocked isocyanate prepolymer;
[0099] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.25 at 25° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0100] Example 4
[0101] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0102] (1) reacting a small molecule diol 1,4-butanediol and trimellitic anhydride at a molar ratio of 1.01:2 at 120°C in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.7% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0103] (2) reacting the product obtained in step (1) with tetradecyl glycidyl ether in a molar ratio of 1:2.5 at 110° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2% of the mass of tetradecyl glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0104] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is 1 times the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 80° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0105] (4) reacting TMXDI with a mixed polyol of PTMEG (number average molecular weight 2000) / PPG (number average molecular weight 1000) (the mass proportion of PTMEG in the mixed polyol is 60%) at 110°C for 3 hours, wherein the molar ratio of TMXDI to the mixed polyol is 1:0.25, adding ε-caprolactam to the system after the reaction (the molar ratio of TMXDI to ε-caprolactam is 1:0.75), and reacting at 80°C for 3 hours until the NCO content is less than 0.1%, to obtain a blocked isocyanate prepolymer;
[0106] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.65 at 20° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0107] Example 5
[0108] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0109] (1) reacting a small molecule diol, diethylene glycol, and trimellitic anhydride at a molar ratio of 1:2 at 110° C. in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.8% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0110] (2) reacting the product obtained in step (1) with dodecyl glycidyl ether in a molar ratio of 1:2.5 at 130° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2% of the mass of dodecyl glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0111] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is twice the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 110° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0112] (4) reacting PDI with a mixed polyol of PEG (number average molecular weight 2000) / PPG (number average molecular weight 2000) (the mass proportion of PEG in the mixed polyol is 60%) at 100°C for 5 h, wherein the molar ratio of PDI to the mixed polyol is 1:0.2, adding ε-caprolactam to the system after the reaction (the molar ratio of PDI to ε-caprolactam is 1:0.85), and reacting at 50°C for 4 h until the NCO content is less than 0.1%, thereby obtaining a blocked isocyanate prepolymer;
[0113] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.75 at 30° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0114] Example 6
[0115] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0116] (1) reacting small molecule 1,3-propylene glycol and trimellitic anhydride at a molar ratio of 1.05:2 at 130°C in the presence of a catalyst (p-toluenesulfonic acid, the addition amount being 0.8% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0117] (2) reacting the product obtained in step (1) with dodecyl glycidyl ether in a molar ratio of 1:2 at 110° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2.5% of the mass of dodecyl glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0118] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is twice the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 100° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0119] (4) PDI and PEG (number average molecular weight 1000) / PO3G (number average molecular weight 1000) mixed polyol (PEG accounts for 50% by mass in the mixed polyol) are reacted at 100°C for 5 hours, wherein the molar ratio of PDI to the mixed polyol is 1:0.2. After the reaction, ε-caprolactam is added to the system (the molar ratio of PDI to ε-caprolactam is 1:0.8), and the reaction is carried out at 50°C for 4 hours until the NCO content is less than 0.1%, thereby obtaining a blocked isocyanate prepolymer;
[0120] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.5 at 10° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0121] Example 7
[0122] This embodiment provides a sintered polymer for N-type TOPCON electronic paste, and the preparation method thereof comprises the following steps:
[0123] (1) reacting small molecule 1,4-butanediol and trimellitic anhydride at a molar ratio of 1.03:2 at 120°C in the presence of a catalyst (p-toluenesulfonic acid, added in an amount of 0.6% of the total mass of the small molecule diol and trimellitic anhydride) until the hydroxyl value is less than 5 mgKOH / g;
[0124] (2) reacting the product obtained in step (1) with dodecyl glycidyl ether in a molar ratio of 1:2 at 120° C. in the presence of a catalyst (triphenylphosphine, added in an amount of 2% of the mass of dodecyl glycidyl ether) until the epoxy value is less than 0.03 eq / 100 g;
[0125] (3) adding γ-glycidyloxypropyltrimethoxysilane (KH560, the amount of which is 1 times the molar number of the product obtained in step (1)) to the reaction system obtained in step (2) and reacting at 100° C. until the acid value of the final product is less than 5 mgKOH / g to obtain a coupling agent-modified epoxy oligomer;
[0126] (4) reacting XDI with a mixed polyol of PEG (number average molecular weight 2000) / PO3G (number average molecular weight 2000) (the mass proportion of PEG in the mixed polyol is 50%) at 80°C for 7 hours, wherein the molar ratio of XDI to the mixed polyol is 1:0.25, adding 3,5-dimethylpyrazole to the system after the reaction (the molar ratio of XDI to 3,5-dimethylpyrazole is 1:0.8), and reacting at 50°C for 4 hours until the NCO content is less than 0.1%, thereby obtaining a blocked isocyanate prepolymer;
[0127] (5) The coupling agent-modified epoxy oligomer and the blocked isocyanate prepolymer are mixed at a mass ratio of 1:0.6 at 25° C. to obtain the sintered polymer for the N-type TOPCON electronic paste.
[0128] Example 8
[0129] Different from Example 1, in step (4), PDI is reacted with PTMEG (number average molecular weight 2000) polyol, wherein the molar ratio of PDI to polyol is 4:1, which is the same as that in Example 1.
[0130] Example 9
[0131] Different from Example 1, in step (4), PDI is reacted with PPG (number average molecular weight 2000) polyol, wherein the molar ratio of PDI to polyol is 4:1, which is the same as that in Example 1.
[0132] Comparative Example 1
[0133] The only difference from Example 1 is that step (3) is not included, and the product obtained in step (2) and the blocked isocyanate prepolymer obtained in step (4) are mixed in a mass ratio of 6:4 to obtain a sintered polymer for N-type TOPCON electronic paste.
[0134] Comparative Example 2
[0135] The only difference from Example 1 is that step (4) is to react PDI with a PTMEG / PPG mixed polyol (the mass proportion of PTMEG in the mixed polyol is 50%), wherein the molar ratio of PDI to the mixed polyol is 4:1, to obtain an isocyanate prepolymer, and then the isocyanate groups are consumed by ethanol to NCO < 0.1%; and then the coupling agent-modified epoxy oligomer obtained in step (2) is mixed with the isocyanate prepolymer in a mass ratio of 1:0.66 to obtain a sintered polymer for N-type TOPCON electronic paste.
[0136] The polymers prepared in the above examples and comparative examples are used in N-type TOPCON electronic paste, as follows:
[0137] The polymer prepared in the embodiment and the comparative example was added in an amount of 0.3 wt % to a commercially available Heraeus slurry with the brand name SOL8200, and a serpentine pattern was printed on an ITO glass using the electronic slurry. After printing, the slurry was baked at a constant temperature of 160° C. for 3 minutes, and then the temperature was increased. The slurry was then placed in a high-temperature oven at 850° C., baked for 5 minutes, and then taken out for cooling.
[0138] The following performance tests were performed:
[0139] (1) Adhesion at 25°C: refer to GB / T 9286-2021, the best is level 0 and the worst is level 5.
[0140] (2) Boiling adhesion: Boil in water at 100°C for 6 hours, take out and cool, and then test the adhesion again.
[0141] (3) Resistance value after boiling: After boiling, use a micro-ohmmeter to test the resistance value at both ends.
[0142] The test results are shown in Table 1.
[0143] Table 1
[0144]
[0145] Examples 1-9 adopt the technology of the present invention, and have good adhesion at room temperature and after boiling in water, and low resistance after boiling in water. Comparative Examples 1-2 do not contain coupling agents or isocyanate groups, and their adhesion and resistance properties after boiling in water are greatly reduced.
[0146] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the sintered polymer for N-type TOPCON electronic paste and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a sintered polymer for N-type TOPCON electronic paste, characterized in that: The preparation method comprises the following steps: (1) reacting a small molecule diol with trimellitic anhydride; (2) reacting the product obtained in step (1) with glycidyl ether; (3) adding a coupling agent, γ-glycidyloxypropyltrimethoxysilane, to the reaction system obtained in step (2) to carry out a reaction to obtain a coupling agent-modified epoxy oligomer; (4) reacting isocyanate with polyol, and then adding a blocking agent to react to obtain a blocked isocyanate prepolymer; (5) The coupling agent-modified epoxy oligomer is mixed with the blocked isocyanate prepolymer to obtain the sintered polymer for the N-type TOPCON electronic paste.
2. The preparation method according to claim 1, characterized in that: The small molecule diol in step (1) is selected from any one of diethylene glycol, 1,3-propylene glycol, and 1,4-butanediol, or a combination of at least two thereof; In step (1), the molar ratio of the small molecule diol to trimellitic anhydride is 1-1.05:2; The reaction in step (1) is carried out in the presence of a catalyst; the catalyst is selected from p-toluenesulfonic acid; The amount of the catalyst added is 0.6-0.8% of the total mass of the small molecule diol and trimellitic anhydride; The reaction temperature of step (1) is 110-130° C.; the reaction of step (1) is carried out until the hydroxyl value is lower than 5 mgKOH / g.
3. The preparation method according to claim 1, characterized in that: The glycidyl ether in step (2) is selected from any one of n-butyl glycidyl ether, dodecyl glycidyl ether or tetradecyl glycidyl ether, or a combination of at least two thereof; Step (2) The molar ratio of the product obtained in step (1) to glycidyl ether is 1:2-3; The reaction in step (2) is carried out in the presence of a catalyst, and the catalyst is selected from triphenylphosphine; The amount of the catalyst used is 2-2.5% of the mass of the glycidyl ether; The reaction temperature in step (2) is 110-130°C; The reaction in step (2) is carried out until the epoxy value is lower than 0.03 eq / 100 g.
4. The preparation method according to claim 1, characterized in that: Step (3) the amount of γ- glycidyl ether oxypropyl trimethoxysilane added is 1-2 times the molar number of the product obtained in step (1); The reaction temperature in step (3) is 80-110°C; The reaction in step (3) is carried out until the acid value of the product is lower than 5 mgKOH / g.
5. The preparation method according to claim 1, characterized in that: The molar ratio of isocyanate to polyol in step (4) is 1:0.2-0.33; The isocyanate in step (4) is selected from any one of pentamethylene pentamethylene diisocyanate, meta-xylylene diisocyanate or tetramethylxylylene diisocyanate, or a combination of at least two thereof; The number average molecular weight of the polyol in step (4) is 1000-2000; The polyol in step (4) is selected from any one of polytetramethylene ether glycol, polypropylene glycol, polyethylene glycol, or polytrimethylene ether glycol, or a combination of at least two thereof; The temperature of the reaction of the isocyanate and the polyol in step (4) is 80-110° C. and the reaction time is 3-8 hours.
6. The preparation method according to claim 1, characterized in that: The polyol in step (4) is a combination of polytetramethylene ether glycol and polypropylene glycol, wherein the polytetramethylene ether glycol accounts for 40-80% of the total mass of the polyol; The blocking agent in step (4) is selected from any one of 3,5-dimethylpyrazole, ε-caprolactam or diisopropylamine, or a combination of at least two thereof; The molar ratio of the isocyanate to the blocking agent in step (4) is 1:0.72-0.85; The temperature for reacting the blocking agent in step (4) is 50-80° C. and the reaction time is 3-6 hours.
7. The preparation method according to claim 1, characterized in that: In step (5), the mixing mass ratio of the coupling agent-modified epoxy oligomer to the blocked isocyanate prepolymer is 1:0.25-0.75; The mixing in step (5) is carried out at 10-30°C.
8. The sintered polymer for N-type TOPCON electronic paste prepared by the preparation method according to any one of claims 1 to 7.
9. An N-type TOPCON electronic paste, characterized in that: The N-type TOPCON electronic paste comprises the sintered polymer for N-type TOPCON electronic paste according to any one of claims 1 to 7.
10. An N-type TOPCON photovoltaic module, characterized in that: The raw materials for preparing the N-type TOPCON photovoltaic module include the N-type TOPCON electronic paste according to any one of claims 1-7.
Citation Information
Patent Citations
Yellowing-resistant solvent-free two-component polyurethane laminating adhesive as well as preparation method and application thereof
CN114736645A
Thermoplastic polyurethane and preparation thereof,and polyurethane adhesive
KR1020020007869A